PERFORMANCE EVALUATION OF NaI(Tl) AND LaBr3(Ce) PORTABLE RADIOLOGICAL IDENTIFIERS IN THE IDENTIFICATION OF 226-Ra AND 228-Ra IN SCALES FROM THE PETROLEUM INDUSTRY - Ana Carolina da Cruz dos Anjos da Cruz Izidório; Luciano Santa Rida de Oliveira; Rodrigo Carnero Curzio; Davi Ferreira de Oliveira (Brazilian Journal of Radiation Sciences, 2022)
The scales from the oil industry are constantly being studied, due to their formation problem, which reduces the plant's production capacity, and the radioactivity in them, which originates from production wells (NORM), which can lead workers to significant exposures. The extraction process makes these scales radioactive, as the 226-Ra and 228-Ra that are mobilized precipitate with the scales. These are directly responsible for the dose increase to which workers are exposed during routine maintenance. In this study, ten scale samples were analyzed, taken from different parts of an oil production plant, using portable radiological identifiers of NaI(Tl) and LaBr3(Ce) to assess the dose rates and performance of these equipment in detection 226-Ra and 228-Ra. The identification of 226-Ra, was given by its daughter 214-Pb and 214-Bi, energies of 295.222 keV and 351.93 keV; and 609.32 keV, respectively. The identification of 228-Ra, by his daughter 212-Pb and 208-Tl, energies of 238.632 keV; and 583.187 keV and 2614.511 keV, respectively. The energy of 583.187 keV appeared only in the spectra obtained with the PRI of LaBr3(Ce). The energy of 2614.511 keV of 208-Tl was discriminated in all spectra obtained with NaI(Tl). The NaI(Tl) PRI performed better due to its better counting efficiency. The identifiers were able to identify 226-Ra and 228-Ra in inlays containing NORM. It was concluded that the PRIs allow fast analysis even in samples with little mass.